To What Extent is the Consumption of the Brand MyProtein linked to Male Identity within the University of Nottingham Context? - Sinanovic, Melissa (2017)
With an evolving society where feminism is on the rise, masculinity is under threat and male identities are being driven into a state of ontological insecurity. This Dissertation explores how the consumption of the brand MyProtein, who sell sports supplements and gym accessories, is used throughout the male population of the University of Nottingham in order to reaffirm traditional hegemonic ideals, and to re-establish confidence and dominance within their identities. Fourteen in-depth interviews are carried out with men who are consumers of MyProtein. Their narratives imply that personal factors such as confidence within their masculinity as well as the the extended-self, which includes sub-cultural groups and peers, play a large influence in creating symbolic meaning that is associated with the brand. This symbolic meaning is in turn used to reaffirm masculine associations to their identity. MyProtein is thus not only a product used to be better at the gym, but becomes a tool for adding gendered meaning to ones identity, and becomes a method for reclaiming and reaffirming masculinity.